Proposta para avaliar a interação oral em língua espanhola: guia didático para professores - Soares, Franciane de Araújo (Brasil, 2020)
This guide shows a proposal of teaching, learning and evaluation of oral interaction in Spanish language. It goals is support teachers into practices of evaluation in Extracurricular courses and Open languages courses mainly. The bases and resources presented in this guide can assist the process of evaluation of this communicative hability, whose aim is identify the level of proficiency of the students in the target-language. For this purpose, necessary instructions are shown in order to use the proposal raised, building new standards of evaluation or adaptation to be performed by the teachers, according to their goals.